Knowledge And Attitude Relationship With Compliance Diet Of Type II Diabetes Mellitus Patients At Home Grandmed Hurt Of Lubuk Pakam - Wira Maria Ginting; Widyana Pratiwi (Jurnal EduHealth, 2021)
Diabetes mellitus (DM) is the oldest disease in the world and is related to the metabolism of glucose levels in the blood. DM can be seen from several sets of aspects of symptoms that arise in a person due to an increase in blood sugar levels (hyperglycemia) due to insulin deficiency. The high prevalence of DM, which is mostly classified as type II DM, is due to the interaction between factors of genetic susceptibility and exposure to the environment. Factors that influence adherence to the type II DM diet include the knowledge and attitudes of people with type II DM. The diabetes mellitus diet is an important part of the comprehensive management of the Type DM diet. The purpose of this study was to determine the relationship of knowledge and attitudes with dietary adherence of people with type II diabetes mellitus. The type of research used is quantitative with analytical design and cross-sectional approach, the number of people in this study is 35 people. The technique of taking sempel in purposive sampling research. The results showed that there was a relationship of knowledge with dietary adherence of people with type II DM (p Value = 0.017) and there was a relationship of attitudes with dietary compliance of people with type II DM (p Value = 0.044). Suggested to the officer. Hospitals are expected to provide special education about diabetes mellitus to patients either in groups or individuals for patients and patients' families.